Formation of heterogeneous multi-agent systems under min-weighted persistent graph. (2017) - Sun, Yanlong; Xu, Ziqiang; Zhang, Xiaoning; Yan, Jing; Chen, Cailian; Guan, Xinping
In this paper, we develop a simple and efficient formation control framework for heterogeneous multi-agent systems under min-weighted persistent graph. As the ability of each agent may be different, the architecture of agents is considered to be heterogeneous. To reduce the communication complexity of keeping connectivity for agents, a topology optimisation scheme is proposed, which is based on min-weighted persistent graph. According to the topology of agents, a directed acyclic graph (DAG) is constructed to reflect the signal flow relation of agents, and then the corresponding formation control protocol is designed by using the transfer function model. Apply the proposed method, it is shown that the communication complexity of multi-agent systems is decreased, and the connection safety is improved. Based on signal flow graph analysis and Mason's rule, the convergence conditions are provided to show the agents can keep a formation. Finally, several simulations are worked out to illustrate the effectiveness of our theoretical results.